Solid lubricant, sliding member, and method for forming a solid lubricant

JP7936815B2Active Publication Date: 2026-10-16IDEMITSU KOSAN CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023561574
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-11-16
Filing Date
2022-11-11
Publication Date
2026-10-16
Estimated Expiration
2042-11-11

Smart Images

  • Figure 0007936815000002
    Figure 0007936815000002
  • Figure 0007936815000003
    Figure 0007936815000003
  • Figure 0007936815000004
    Figure 0007936815000004
Patent Text Reader

Abstract

The present invention provides a solid lubricant material which has high durability. This solid lubricant material has a material that has a hexagonal crystal structure. The ratio of planes other than the (002) plane to the (002) plane at the interface between the solid lubricant material and a base material coated therewith is higher than the ratio of planes other than the (002) plane to the (002) plane in the surface of the solid lubricant material. Alternatively, the ratio of the X-ray diffraction peak intensity of planes other than the (002) plane to the X-ray diffraction peak intensity of the (002) plane at the interface between the solid lubricant material and a base material coated therewith is higher than the ratio of the X-ray diffraction peak intensity of planes other than the (002) plane to the X-ray diffraction peak intensity of the (002) plane in the surface of the solid lubricant material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a solid lubricant, a sliding member, and a method for forming a solid lubricant.

Background Art

[0002] One of the measures for energy saving is reducing the frictional force of movable parts. Various solid lubricants are used for the purpose of friction reduction. The following Patent Document 1 and Patent Document 2 disclose zinc oxide coatings as solid lubricants. In Patent Document 1, a low-friction ZnO coating is disclosed that includes (002) and (103) planes, and contains (100), (101), (102) and (104) planes in a smaller proportion than the (002) and (103) planes for achieving low friction.

Prior Art Documents

Patent Documents

[0003]

Patent Document 1

Patent Document 2

Summary of the Invention

[0004] It is preferable that the solid lubricant has a low friction coefficient. In addition to this, improvement in the durability of the solid lubricant is also demanded. In particular, depending on the environment in which the solid lubricant is used, further enhanced durability of the solid lubricant may be desired.

[0005] A solid lubricant according to one embodiment comprises a material having a hexagonal crystal structure. In this solid lubricant, the ratio of non-(002) planes to (002) planes at the interface between the solid lubricant and the substrate to be coated is higher than the ratio of non-(002) planes to (002) planes at the surface of the solid lubricant. Alternatively, the ratio of the peak intensity of X-ray diffraction of non-(002) planes to the peak intensity of X-ray diffraction of (002) planes at the interface between the solid lubricant and the substrate is higher than the ratio of the peak intensity of X-ray diffraction of non-(002) planes to the peak intensity of X-ray diffraction of (002) planes at the surface of the solid lubricant.

[0006] A method for forming a solid lubricant according to one embodiment relates to a method for forming a solid lubricant having a material having a hexagonal crystal structure. The forming method includes the step of coating a substrate with zinc oxide such that the ratio of the surface other than the (002) plane to the (002) plane at the interface with the substrate to be coated is higher than the ratio of the surface other than the (002) plane to the (002) plane at the surface, or the ratio of the peak intensity of X-ray diffraction of the surface other than the (002) plane to the peak intensity of X-ray diffraction of the (002) plane at the interface with the substrate to the ratio of the peak intensity of X-ray diffraction of the surface other than the (002) plane at the surface is higher than the ratio of the peak intensity of X-ray diffraction of the surface other than the (002) plane to the peak intensity of X-ray diffraction of the (002) plane at the surface.

[0007] A sliding member according to one embodiment has the aforementioned solid lubricant. [Brief explanation of the drawing]

[0008] [Figure 1] Figure 1 is a schematic diagram showing an example of the configuration of a solid lubricant and a structure using the same according to the first embodiment. [Figure 2] Figure 2 is a graph showing the results of X-ray diffraction near the interface between the substrate and zinc oxide coatings used as various solid lubricants. [Figure 3] Figure 3 is a schematic diagram showing an example of the configuration of a solid lubricant and a structure using the same according to the second embodiment. [Figure 4] Figure 4 is a schematic diagram showing an example of the configuration of a solid lubricant and a structure using the same according to the third embodiment. [Figure 5] Figure 5 is a graph showing the results of surface-side X-ray diffraction tests for various zinc oxide coatings. [Figure 6] Figure 6 shows laser microscope images of the substrate surface in Example 2 and Reference Example 1 after the reciprocating friction test. [Figure 7] Figure 7 is a graph showing the measurement results of the friction coefficient on the surface of the substrate in Examples 1 and 2 and Reference Example 1 during the reciprocating friction test. [Modes for carrying out the invention]

[0009] The embodiments will be described below with reference to the drawings. In the following drawings, identical or similar parts are denoted by the same or similar reference numerals. However, it should be noted that the drawings are schematic, and the proportions of the dimensions, etc., may differ from those of reality.

[0010] [First Embodiment] First, an example of the configuration of a solid lubricant and a structure using the same according to the first embodiment will be described. Figure 1 is a schematic diagram showing an example of the configuration of a solid lubricant and a structure using the same according to the first embodiment.

[0011] The structure may include a base material 200, a solid lubricant 100, and a lubricating oil 300. Here, the solid lubricant 100 is provided on the base material 200. The base material 200 is the material on which the solid lubricant is to be provided. The material constituting the base material 200 is not particularly limited, but may be a metal member such as a steel plate. In the example shown in Figure 1, the lubricating oil 300 is present on the solid lubricant. Alternatively, the lubricating oil 300 may not be used.

[0012] The solid lubricant 100 includes materials having a hexagonal crystal structure. For example, the solid lubricant 100 includes materials selected from the group having ZnO, BeO, SiO2, GeO2, Al2O3, WO3, MoO3, and MoS2.

[0013] The material having a hexagonal crystal structure is preferably an oxide material. Examples of such oxide materials include ZnO, BeO, SiO2, GeO2, Al2O3, WO3, and MoO3. More preferably, the material constituting the solid lubricant 100 is zinc oxide (ZnO).

[0014] In the embodiment shown in Figure 1, the solid lubricant 100 may have a base layer 110 on the substrate 200 side and a surface layer 120 on the surface side. However, it should be noted that the base layer 110 and the surface layer 120 do not need to be separated by a clear boundary.

[0015] The solid lubricant 100 can be formed by a film deposition technique such as sputtering. In this case, the underlayer 110 and the surface layer 120 of the solid lubricant 100 may be layers formed by different film deposition conditions.

[0016] The underlayer 110 is located at the interface with the substrate 200. The surface layer 120 is oriented away from the underlayer 110. In the first embodiment, the crystal orientation of the underlayer 110 is different from that of the surface layer 120.

[0017] More specifically, the ratio of non-(002) surfaces to (002) surfaces of the solid lubricant at the interface with the substrate being coated is higher than the ratio of non-(002) surfaces to (002) surfaces on the surface of the solid lubricant. In other words, the ratio of the peak intensity of X-ray diffraction for non-(002) surfaces to the peak intensity of X-ray diffraction for (002) surfaces of the solid lubricant at the interface with the substrate being coated is higher than the ratio of the peak intensity of X-ray diffraction for non-(002) surfaces to the peak intensity of X-ray diffraction for (002) surfaces on the surface of the solid lubricant.

[0018] Preferably, the ratio of the (100) plane and the (101) plane to the (002) plane of the solid lubricant at the interface with the substrate to be coated is higher than the ratio of the (100) plane and the (101) plane to the (002) plane on the surface of the solid lubricant. In other words, the ratio of the X-ray diffraction peak intensities for the (100) plane and the (101) plane to the X-ray diffraction peak intensity for the (002) plane at the interface with the substrate to be coated is higher than the ratio of the X-ray diffraction peak intensities for the (100) plane and the (101) plane to the X-ray diffraction peak intensity for the (002) plane on the surface of the solid lubricant.

[0019] The (002) plane of a material having a hexagonal crystal structure is the closest-packed plane, and the (002) plane of the material is considered to be a low-friction surface. Therefore, if most of the interface between the substrate and the solid lubricant corresponds to the (002) plane (low-friction surface) of the solid lubricant, the solid lubricant tends to peel off from the substrate, and the durability of the solid lubricant is considered to decrease. In this embodiment, planes other than the (002) plane of the solid lubricant are relatively abundantly contained at the interface between the substrate and the solid lubricant. Therefore, the solid lubricant is less likely to peel off from the substrate, and the durability of the solid lubricant is considered to be improved. In consideration of this effect, it is considered that the durability of the solid lubricant can be improved regardless of the presence or absence of lubricating oil on the surface of the solid lubricant.

[0020] On the other hand, since the surface of the solid lubricant has a relatively high proportion of the (002) plane, the low friction property of the solid lubricant can be maintained.

[0021] The proportion of the (002) plane in each layer of the solid lubricant and the X-ray diffraction peak intensity related to the (002) plane can be changed by adjusting the film formation conditions during the film formation of the solid lubricant.

[0022] Figure 2 is a table showing the results of X-ray diffraction tests on zinc oxide coatings as solid lubricants. The upper line in the graph of Figure 2 represents the results when a zinc oxide coating is formed on a substrate by sputter deposition using a zinc oxide target material under conditions where the oxygen partial pressure relative to argon is 20%. The lower line in the graph of Figure 2 represents the results when a zinc oxide coating is formed on a substrate by sputter deposition using a zinc oxide target material under conditions where the oxygen partial pressure relative to argon is 0% (oxygen-free conditions).

[0023] As shown in Figure 2, increasing the oxygen partial pressure in the noble gas increases the ratio of the X-ray diffraction peak intensity for the (100) and (101) planes to the peak intensity for the (002) plane. This means that the proportion of the (100) and (101) planes to the (002) plane on the surface of the coating is increased. Thus, by adjusting the oxygen partial pressure during sputter deposition, it is possible to adjust the ratio of the X-ray diffraction peak intensity for other planes to the peak intensity for the (002) plane, and the proportion of other planes to the (002) plane. Therefore, by appropriately adjusting the oxygen partial pressure during sputter deposition of the underlayer and surface layer, it is possible to realize the zinc oxide coating described above.

[0024] Next, a method for forming a solid lubricant will be described. The method for forming a solid lubricant includes the step of coating a substrate with a solid lubricant such that the ratio of the surface other than the (002) surface to the (002) surface at the interface with the substrate to be coated is higher than the ratio of the surface other than the (002) surface to the (002) surface at the surface, or the ratio of the peak intensity of X-ray diffraction for the surface other than the (002) surface to the peak intensity of X-ray diffraction for the (002) surface at the interface with the substrate to be coated is higher than the ratio of the peak intensity of X-ray diffraction for the surface other than the (002) surface to the peak intensity of X-ray diffraction for the (002) surface at the surface.

[0025] Preferably, in the above step, a solid lubricant is coated onto the substrate such that the ratio of the (100) plane and (101) plane to the (002) plane at the interface with the substrate to be coated is higher than the ratio of the (100) plane and (101) plane to the (002) plane at the surface, or the ratio of the peak intensity of X-ray diffraction for the (100) plane and (101) plane to the peak intensity of X-ray diffraction for the (002) plane at the interface with the substrate to be coated is higher than the ratio of the peak intensity of X-ray diffraction for the (100) plane and (101) plane to the peak intensity of X-ray diffraction for the (002) plane at the surface.

[0026] In the first embodiment, the solid lubricant 100 is formed to have at least a base layer 110 located at the interface with the substrate 200 and a surface layer 120 facing away from the base layer. In this case, the film formation conditions for forming the surface layer 120 may be different from the film formation conditions for forming the base layer 110.

[0027] Here, the solid lubricant may be coated using any film deposition technique, such as sputtering. The ratio of non-(002) planes to (002) planes in each layer of the solid lubricant, and the ratio of X-ray diffraction peak intensities between the (002) planes and the non-(002) planes, can be changed by adjusting the film deposition conditions during coating of the solid lubricant.

[0028] In one example, a solid lubricant is coated by sputtering. In this case, the crystal orientation of the solid lubricant can be changed by altering the ratio of another gas to the noble gas during sputtering near the interface with the substrate, compared to the ratio of the other gas to the noble gas during sputtering near the surface.

[0029] When the solid lubricant contains an oxide material, it is preferable that the oxygen content relative to the noble gas during sputter deposition near the interface with the substrate is higher than the oxygen content relative to the noble gas during sputter deposition near the surface. This makes it possible to achieve the ratio of non-(002) planes to (002) planes and the ratio of X-ray diffraction peak intensities between (002) planes and non-(002) planes in each layer of the solid lubricant, as in the zinc oxide deposition example described above. These ratios can also be adjusted by changing the oxygen content relative to the noble gas.

[0030] In sputter deposition, the target material is not particularly limited as long as it can form a solid lubricant. If the solid lubricant has an oxide material, the target material may be an oxide material containing the molecules that make up the oxide material, or it may be a material from which oxygen has been removed from the molecules that make up the oxide material. From the viewpoint of reducing the oxygen content in the gas surrounding the target material, the target material may be a material containing the same molecules as the oxide material that makes up the solid lubricant.

[0031] For example, if the solid lubricant is made of zinc oxide, the target material may be, for example, zinc oxide or zinc. From the viewpoint of reducing the oxygen content in the gas surrounding the target material, the target material is preferably zinc oxide.

[0032] The gas surrounding the target material may be a noble gas or a mixture of oxygen and a noble gas. The noble gas may be, for example, argon.

[0033] [Second Embodiment] The following describes an example of the configuration of a solid lubricant and a structure using the same according to the second embodiment. Figure 3 is a schematic diagram showing an example of the configuration of a solid lubricant and a structure using the same according to the second embodiment. Components similar to those in the first embodiment are denoted by the same reference numerals. Note that the description of components similar to those in the first embodiment may be omitted.

[0034] In the second embodiment, the solid lubricant 100 may have a base layer 110, an intermediate layer 130, and a surface layer 120. The base layer 110 is a layer that is in contact with the base material 200. The surface layer 120 is a surface that can slide against other members. The intermediate layer 130 is located between the base layer 110 and the surface layer 120.

[0035] The base layer 110, the intermediate layer 130, and the surface layer 120 may be layers formed by different film deposition conditions, for example. Here, only one intermediate layer 130 is shown in Figure 3. Alternatively, the solid lubricant 100 may have multiple intermediate layers 130 between the base layer 110 and the surface layer 120. In this case, the multiple intermediate layers 130 may be layers formed by different film deposition conditions.

[0036] In the second embodiment, it should be noted that the base layer 110, the intermediate layer 130, and the surface layer 120 do not necessarily have to be separated by a clear boundary.

[0037] In the second embodiment, the crystal orientation of the base layer 110 is different from that of the surface layer 120. The crystal orientation of the intermediate layer 130 may be different from that of the base layer 110 and the surface layer 120, or it may be the same as that of either the base layer 110 or the surface layer 120.

[0038] Specifically, in the second embodiment as well, the ratio of the non-(002) surface of the solid lubricant to the (002) surface at the interface (underlayer) with the substrate to be coated is higher than the ratio of the non-(002) surface to the (002) surface at the surface (surface layer) of the solid lubricant. In other words, the ratio of the peak intensity of X-ray diffraction for the non-(002) surface to the peak intensity of X-ray diffraction for the (002) surface at the interface with the substrate to be coated is higher than the ratio of the peak intensity of X-ray diffraction for the non-(002) surface to the peak intensity of X-ray diffraction for the (002) surface at the surface of the solid lubricant. As a result, a highly durable solid lubricant can be expected, similar to the first embodiment.

[0039] [Third Embodiment] The following describes an example of the configuration of a solid lubricant and a structure using the same according to the third embodiment. Figure 4 is a schematic diagram showing an example of the configuration of a solid lubricant and a structure using the same according to the third embodiment. Components similar to those in the first embodiment are denoted by the same reference numerals. Note that the description of components similar to those in the first embodiment may be omitted.

[0040] In the third embodiment, the solid lubricant 100 is formed by layers without distinct boundaries. In the third embodiment, the crystal orientation of the materials constituting the solid lubricant changes gradually with respect to the thickness direction.

[0041] Even in this case, the ratio of non-(002) surfaces to (002) surfaces of the solid lubricant at the interface with the substrate being coated is higher than the ratio of non-(002) surfaces to (002) surfaces on the surface of the solid lubricant. In other words, the ratio of the peak intensity of X-ray diffraction for non-(002) surfaces to the peak intensity of X-ray diffraction for (002) surfaces of the solid lubricant at the interface with the substrate being coated is higher than the ratio of the peak intensity of X-ray diffraction for non-(002) surfaces to the peak intensity of X-ray diffraction for (002) surfaces on the surface of the solid lubricant. As a result, a highly durable solid lubricant can be expected.

[0042] The solid lubricant 100 according to the third embodiment can be formed by gradually changing the film formation conditions of the solid lubricant along with the lamination of the solid lubricant. When the solid lubricant has an oxide material, the solid lubricant can be formed by gradually changing the oxygen content relative to the noble gas during sputter deposition while the film formation of the solid lubricant progresses. Specifically, the oxygen content relative to the noble gas during sputter deposition can be gradually reduced along with the lamination of the solid lubricant 100. This makes it possible to realize a solid lubricant in which the crystal orientation of the materials constituting the solid lubricant gradually changes with thickness.

[0043] [Example 1] Next, the solid lubricant according to Example 1 will be described. In Example 1, a zinc oxide coating is provided on the substrate as the solid lubricant. As shown in Figure 1, the zinc oxide coating includes a base layer and a surface layer. The base layer and surface layer of the zinc oxide coating were formed using the "ULVAC SIH-300 Intervac sputtering system". The target material was zinc oxide.

[0044] In Example 1, the deposition gas used during the deposition of the zinc oxide underlayer was a mixture of 80% argon and 20% oxygen (see Table 1). In Example 1, the deposition gas used during the deposition of the surface layer was argon, and did not contain oxygen. The deposition gas flow rate was 50 ml / min. The deposition temperature was 25°C, and the deposition pressure was 0.5 Pa. The discharge power during the deposition of the underlayer was 200 W, and the discharge power during the deposition of the surface layer was 2000 W. The film thickness of the underlayer was 40 nm, and the film thickness of the surface layer was 1700 nm. The aforementioned film thicknesses were measured by spectroscopic ellipsometry (the same applies hereafter).

[0045] [Example 2] The solid lubricant according to Example 2 will now be described. In Example 2, a zinc oxide coating is provided on the substrate as the solid lubricant. The zinc oxide coating according to Example 2 was formed under the same conditions as in Example 1, except for the thickness of the zinc oxide underlayer (see Table 1). In Example 2, the thickness of the underlayer was 80 nm, and the thickness of the surface layer was 1700 nm.

[0046] [Reference example 1] The solid lubricant in Reference Example 1 will now be described. In Reference Example 1, a zinc oxide coating is provided on the substrate as the solid lubricant. The zinc oxide coating in Reference Example 1 was formed under the same conditions as in Example 1, except for the components of the film-forming gas used during the formation of the underlayer. In Reference Example 1, the film-forming gas used during the formation of the underlayer and surface layer was argon, and did not contain oxygen (see Table 1). In Reference Example 1, the film thickness of the underlayer was 60 nm, and the film thickness of the surface layer was 1700 nm.

[0047] (Table 1) TIFF0007936815000001.tif28153

[0048] In Examples 1 and 2, the partial pressure of oxygen in the deposition gas during the deposition of the underlayer is higher than the partial pressure of oxygen in the deposition gas during the deposition of the surface layer. Therefore, as explained in Figure 2, the ratio of non-(002) faces to (002) faces of zinc oxide at the interface with the substrate to be coated is considered to be higher than the ratio of non-(002) faces to (002) faces on the surface of zinc oxide. In other words, the ratio of the peak intensity of X-ray diffraction for non-(002) faces to the peak intensity of X-ray diffraction for (002) faces of zinc oxide at the interface with the substrate to be coated is higher than the ratio of the peak intensity of X-ray diffraction for non-(002) faces to the peak intensity of X-ray diffraction for (002) faces on the surface of zinc oxide.

[0049] In Reference Example 1, the ratio of non-(002) faces to (002) faces of zinc oxide at the interface with the substrate to be coated is considered to be substantially the same as the ratio of non-(002) faces to (002) faces on the surface of zinc oxide. In other words, the ratio of the peak intensity of X-ray diffraction of non-(002) faces to the peak intensity of X-ray diffraction of the (002) faces of zinc oxide at the interface with the substrate to be coated is considered to be substantially the same as the ratio of the peak intensity of X-ray diffraction of non-(002) faces to the peak intensity of X-ray diffraction of the (002) faces on the surface of zinc oxide.

[0050] Figure 5 is a graph showing the results of surface-side X-ray diffraction tests for various zinc oxide coatings. In Figure 5, X-ray diffraction tests were performed by irradiating the surface side of the zinc oxide coatings according to Examples 1, 2 and Reference Example 1 with X-rays. In Examples 1, 2 and Reference Example 1, the peak intensity of X-ray diffraction related to the (002) plane of zinc oxide is high. In Examples 1, 2 and Reference Example 1, the surface layers of zinc oxide were formed under the same deposition conditions. Therefore, the peak intensities of X-ray diffraction in Examples 1, 2 and Reference Example 1 are almost the same.

[0051] On the other hand, as already explained using Figure 2, in the underlayers of Examples 1 and 2, increasing the partial pressure of oxygen in the noble gas during film formation increases the ratio of the peak intensity of X-ray diffraction for the (100) and (101) planes to the peak intensity of X-ray diffraction for the (002) plane. Therefore, in Examples 1 and 2, the ratio of the peak intensity of X-ray diffraction for planes other than the (002) plane to the peak intensity of X-ray diffraction for the (002) plane of zinc oxide at the interface with the substrate to be coated is higher than the ratio of the peak intensity of X-ray diffraction for planes other than the (002) plane to the peak intensity of X-ray diffraction for the (002) plane on the surface of zinc oxide. This means that the ratio of planes other than the (002) plane to the (002) plane at the interface with the substrate to be coated is higher than the ratio of planes other than the (002) plane to the (002) plane on the surface.

[0052] A reciprocating friction test was performed on substrates having a zinc oxide coating according to Example 2 and Reference Example 1. In the reciprocating friction test, a ball made of steel (SUJ-2) with a diameter of 0.5 inches was moved back and forth on the surface of the substrate with the zinc oxide coating. Here, the reciprocating friction test was performed with machine oil applied to the zinc oxide coating.

[0053] A sphere made of steel was pressed against a substrate with a load of 3 kgf and moved back and forth on the substrate. The temperature during the test was room temperature. The stroke width of the steel sphere was 20 mm, and the stroke speed was 10 mm / s. The steel sphere was also moved back and forth on a substrate 200 having a zinc oxide coating.

[0054] Figure 6 shows laser microscope images of the substrate surface in Example 2 and Reference Example 1 after the reciprocating friction test. From Figure 6, it can be seen that the zinc oxide coating in Example 2 hardly peeled off even after the reciprocating friction test. In contrast, the zinc oxide coating in Reference Example 1 partially peeled off after the reciprocating friction test. From these results, it can be seen that the durability of the zinc oxide coating in Example 2 has been improved.

[0055] Figure 7 is a graph showing the measurement results of the friction coefficient on the surface of the substrate in Examples 1 and 2 and Reference Example 1 during the reciprocating friction test. From Figure 7, it can be seen that in Examples 1 and 2, the friction coefficient remains stable even as the number of sliding cycles of the steel ball increases. In contrast, in Reference Example 1, the friction coefficient suddenly increases around the 20th sliding cycle, and then gradually increases after exceeding the 70th sliding cycle. Thus, the friction coefficient of the zinc oxide coating in Examples 1 and 2 maintains a more stable value than the friction coefficient of the zinc oxide coating in Reference Example 1.

[0056] Furthermore, comparing Example 1 and Example 2, it can be seen that the coefficient of friction of the zinc oxide coating remains lower as the thickness of the underlying layer increases. In particular, the coefficient of friction of the zinc oxide coating according to Example 2 can stably maintain a low value.

[0057] The solid lubricant of the present invention can be suitably applied to sliding members having a sliding surface. The solid lubricant is provided on the sliding surface of the sliding member, and the sliding surface corresponds to the surface of the aforementioned base material 200. Examples of sliding members include bearings, seals, flywheels, scissors, plunger pumps, pistons, gears, crankshafts, artificial joints, and the like.

[0058] This application claims priority under Japanese Patent Application No. 2021-186703, filed on 16 November 2021, the entire contents of said patent application are incorporated herein by reference.

[0059] As described above, the content of the present invention has been disclosed through embodiments and examples, but the descriptions and drawings that constitute part of this disclosure should not be understood as limiting the present invention. Various alternative embodiments, examples, and operational techniques will become apparent to those skilled in the art from this disclosure. Therefore, the technical scope of the present invention is defined solely by the inventive features relating to the claims that are reasonable from the above description.

Claims

1. A solid lubricant comprising a material having a hexagonal crystal structure, The material having a hexagonal crystal structure is an oxide material, The ratio of non-(002) surfaces to (002) surfaces at the interface with the substrate to be coated is higher than the ratio of non-(002) surfaces to (002) surfaces on the surface, or A solid lubricant wherein the ratio of the peak intensity of X-ray diffraction for surfaces other than the (002) surface to the peak intensity of X-ray diffraction for the (002) surface at the interface with the substrate is higher than the ratio of the peak intensity of X-ray diffraction for surfaces other than the (002) surface to the peak intensity of X-ray diffraction for the (002) surface at the surface.

2. A solid lubricant comprising a material having a hexagonal crystal structure, The solid lubricant is ZnO, BeO, SiO 2 , GeO 2 Al 2 O 3 WO 3 MoO 3 and MoS 2 Includes a material selected from the group having the following characteristics: The ratio of non-(002) surfaces to (002) surfaces at the interface with the substrate to be coated is higher than the ratio of non-(002) surfaces to (002) surfaces on the surface, or A solid lubricant wherein the ratio of the peak intensity of X-ray diffraction for surfaces other than the (002) surface to the peak intensity of X-ray diffraction for the (002) surface at the interface with the substrate is higher than the ratio of the peak intensity of X-ray diffraction for surfaces other than the (002) surface to the peak intensity of X-ray diffraction for the (002) surface at the surface.

3. A solid lubricant comprising a material having a hexagonal crystal structure, The ratio of (100) and (101) planes to (002) planes at the interface with the substrate to be coated is higher than the ratio of (100) and (101) planes to (002) planes on the surface, or A solid lubricant wherein the ratio of the peak intensity of X-ray diffraction for the (100) and (101) planes at the interface with the substrate to the peak intensity of X-ray diffraction for the (002) plane is higher than the ratio of the peak intensity of X-ray diffraction for the (100) and (101) planes at the surface to the peak intensity of X-ray diffraction for the (002) plane.

4. A solid lubricant comprising a material having a hexagonal crystal structure, The ratio of non-(002) surfaces to (002) surfaces at the interface with the substrate to be coated is higher than the ratio of non-(002) surfaces to (002) surfaces on the surface, or The ratio of the peak intensity of X-ray diffraction for surfaces other than the (002) surface to the peak intensity of X-ray diffraction for the (002) surface at the interface with the substrate is higher than the ratio of the peak intensity of X-ray diffraction for surfaces other than the (002) surface to the peak intensity of X-ray diffraction for the (002) surface at the surface. The material having a hexagonal crystal structure is a solid lubricant formed from the interface to the surface.

5. The solid lubricant comprises at least a base layer located at the interface with the substrate and a surface layer facing away from the base layer. The solid lubricant according to any one of claims 1 to 4, wherein the crystal orientation of the underlayer is different from that of the surface layer.

6. The solid lubricant according to any one of claims 1 to 4, wherein the crystal orientation of the material constituting the solid lubricant changes gradually with respect to the thickness direction.

7. A method for forming a solid lubricant, comprising the step of coating a substrate with a solid lubricant containing a material having a hexagonal crystal structure, such that the ratio of the (100) plane and the (101) plane to the (002) plane at the interface with the substrate to be coated is higher than the ratio of the (100) plane and the (101) plane to the (002) plane at the surface, or the ratio of the peak intensity of X-ray diffraction for the (100) plane and the (101) plane to the peak intensity of X-ray diffraction for the (002) plane at the interface with the substrate is higher than the ratio of the peak intensity of X-ray diffraction for the (100) plane and the (101) plane at the surface to the peak intensity of X-ray diffraction for the (002) plane at the surface.

8. A solid lubricant comprising a material having a hexagonal crystal structure is coated onto a substrate such that the ratio of the surface other than the (002) plane to the (002) plane at the interface with the substrate is higher than the ratio of the surface other than the (002) plane to the (002) plane at the surface, or the ratio of the peak intensity of X-ray diffraction for the surface other than the (002) plane to the peak intensity of X-ray diffraction for the (002) plane at the interface with the substrate is higher than the ratio of the peak intensity of X-ray diffraction for the surface other than the (002) plane at the surface, The solid lubricant is coated by a sputtering film deposition method. A method for forming a solid lubricant, wherein the oxygen content relative to the noble gas during sputtering deposition at a position close to the interface with the substrate is higher than the oxygen content relative to the noble gas during sputtering deposition at a position close to the surface.

9. The method comprises the step of coating a substrate with a solid lubricant containing a material having a hexagonal crystal structure such that the ratio of the surface other than the (002) plane to the (002) plane at the interface with the substrate to be coated is higher than the ratio of the surface other than the (002) plane to the (002) plane at the surface, or the ratio of the peak intensity of X-ray diffraction for the surface other than the (002) plane to the peak intensity of X-ray diffraction for the (002) plane at the interface with the substrate is higher than the ratio of the peak intensity of X-ray diffraction for the surface other than the (002) plane at the surface, A method for forming a solid lubricant, wherein the material having a hexagonal crystal structure is an oxide material.

10. A solid lubricant comprising a material having a hexagonal crystal structure is coated onto a substrate such that the ratio of the surface other than the (002) plane to the (002) plane at the interface with the substrate is higher than the ratio of the surface other than the (002) plane to the (002) plane at the surface, or the ratio of the peak intensity of X-ray diffraction for the surface other than the (002) plane to the peak intensity of X-ray diffraction for the (002) plane at the interface with the substrate is higher than the ratio of the peak intensity of X-ray diffraction for the surface other than the (002) plane at the surface, The solid lubricant is ZnO, BeO, SiO 2 , GeO 2 , Al 2 O 3 , WO 3 , MoO 3 and MoS 2 A method for forming a solid lubricant, comprising a material selected from the group having

11. A solid lubricant comprising a material having a hexagonal crystal structure is coated onto a substrate such that the ratio of the surface other than the (002) plane to the (002) plane at the interface with the substrate is higher than the ratio of the surface other than the (002) plane to the (002) plane at the surface, or the ratio of the peak intensity of X-ray diffraction for the surface other than the (002) plane to the peak intensity of X-ray diffraction for the (002) plane at the interface with the substrate is higher than the ratio of the peak intensity of X-ray diffraction for the surface other than the (002) plane at the surface, A method for forming a solid lubricant, wherein the material having a hexagonal crystal structure is formed from the interface to the surface.

12. The solid lubricant is formed to have at least a base layer located at the interface with the substrate and a surface layer facing away from the base layer, A method for forming a solid lubricant according to any one of claims 7 to 11, wherein the film formation conditions for forming the surface layer are different from the film formation conditions for forming the underlayer.

13. A method for forming a solid lubricant according to any one of claims 7 to 11, wherein the film formation conditions of the solid lubricant are gradually changed along with the lamination of the solid lubricant.

14. A solid lubricant comprising a material having a hexagonal crystal structure, In the aforementioned solid lubricant, The ratio of non-(002) surfaces to (002) surfaces at the interface with the substrate to be coated is higher than the ratio of non-(002) surfaces to (002) surfaces on the surface, or A sliding member wherein the ratio of the peak intensity of X-ray diffraction for a surface other than the (002) surface to the peak intensity of X-ray diffraction for the (002) surface at the interface with the substrate is higher than the ratio of the peak intensity of X-ray diffraction for a surface other than the (002) surface to the peak intensity of X-ray diffraction for the (002) surface at the surface.

Citation Information

Patent Citations

  • Gallium nitride wafer

    JP2010045397A

  • Sliding member

    JP2010196813A

  • Coating tool having superior wear resistance and slide resistance, and manufacturing method of the same

    JP2012152878A

  • Sliding bearing and method of manufacturing the same

    JP2013210061A

  • Sliding member having chromium nitride film formed thereon

    WO1999031289A1